2019
DOI: 10.1177/0954406219850221
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical strength of adhesively bonded joints using polymeric additive manufacturing

Abstract: This paper investigates the combined use of one of the most widespread additive manufacturing techniques, fused deposition molding, with polymeric materials and structural adhesive. The aim is twofold: first, to enhance the adhesive performance exploiting the capability of the additive manufacturing to tailor the bonding surface of the adherend, and second to overcome one of the main limitations of 3D printing, i.e. the quite small printing volume, by means of adhesive bonding. Bonding multiple parts together … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 32 publications
(39 reference statements)
2
31
0
1
Order By: Relevance
“…FDM is a versatile fabrication method, which allows the design of more complex geometries of the substrates relatively easily, whereas conventional fabrication methods require complex machining of either substrate or moulds [2]. Spaggiari and Denti [11] used single lap joints SLJs) with two adhesives and seven different surface morphologies to study AM bonded joints. They found that the surface morphologies of the adherends had only a small influence on the load capacity and stiffness of the joints.…”
Section: Introductionmentioning
confidence: 99%
“…FDM is a versatile fabrication method, which allows the design of more complex geometries of the substrates relatively easily, whereas conventional fabrication methods require complex machining of either substrate or moulds [2]. Spaggiari and Denti [11] used single lap joints SLJs) with two adhesives and seven different surface morphologies to study AM bonded joints. They found that the surface morphologies of the adherends had only a small influence on the load capacity and stiffness of the joints.…”
Section: Introductionmentioning
confidence: 99%
“…The first approach is used to create a desired pattern able to provide mechanical interlocking and increase the area at the interface between adherend and adhesive. Several authors [ 49 , 50 , 52 , 61 ] used geometrical patterns indented in the adherend thickness to maximize the overlap area, while others [ 23 , 54 ] used patterns protruded in the bondline to seek mechanical interlocking and to alter the strain distribution in the adhesive.…”
Section: Discussionmentioning
confidence: 99%
“…Garcia-Guzman et al [ 52 ] investigated the effect of the structured interfaces seen in the previous works by Spaggiari et al and Cavalcanti et al [ 49 , 50 ] using DCB testing. This experiment was carried out to determine how morphological patterns on the surface of the adherends influence the fracture toughness.…”
Section: Joint Design Strategies For Additive Manufacturingmentioning
confidence: 99%
“…However, as this asks for major hardware changes in the 3D printer, the slow speed factor is sometimes overlooked. Among the various limitations of the 3D printing technology, one of the strongest limitation a 3D printer suffers from is its limited build volume, wherein it cannot straightaway print a part greater than the bed volume (Dugbenoo et al , 2018; Kariz et al , 2017; Leicht et al , 2020; Luo et al , 2012; Song et al , 2015; Spaggiari and Denti, 2019; Yap et al , 2020). It is observed that as the dimensions of the object to be printed increases, it starts affecting the stability, distortions, tolerances and the cost of the printed component.…”
Section: Introductionmentioning
confidence: 99%